Impact of body mass index on long‐term clinical outcomes after second‐generation drug eluting stent implantation: Insights from the international global RESOLUTE program. Issue 6 (17th February 2015) - Diletti, Roberto; Garcia‐Garcia, Hector M.; Bourantas, Christos; Van Mieghem, Nicolas M.; van Geuns, Robert Jan; Muramatsu, Takashi; Zhang, Yao‐Jun; Mauri, Laura; Belardi, Jorge; Silber, Sigmund; Widimsky, Petr; Leon, Martin; et al.
Abstract : Background: An increased body mass index (BMI) is associated with a high risk of cardiovascular disease and reduction in life expectancy. However, several studies reported improved clinical outcomes in obese patients treated for cardiovascular diseases. The aim of the present study is to investigate the impact of BMI on long‐term clinical outcomes after implantation of zotarolimus eluting stents. Methods: Individual patient data were pooled from the RESOLUTE Clinical Program comprising five trials worldwide. The study population was sorted according to BMI tertiles and clinical outcomes were evaluated at 2‐year follow‐up. Results: Data from a total of 5, 127 patients receiving the R‐ZES were included in the present study. BMI tertiles were as follow: I tertile (≤ 25.95 kg/m 2 —Low or normal weight) 1, 727 patients; II tertile (>25.95 ≤ 29.74 kg/m 2 —overweight) 1, 695 patients, and III tertile (>29.74 kg/m 2 —obese) 1, 705 patients. At 2‐years follow‐up no difference was found for patients with high BMI (III tertile) compared with patients with normal or low BMI (I tertile) in terms of target lesion failure (I–III tertile, HR [95% CI] = 0.89 [0.69, 1.14], P = 0.341; major adverse cardiac events (I–III tertile, HR [95% CI] = 0.90 [0.72, 1.14], P = 0.389; cardiac death (I–III tertile, HR [95% CI] = 1.20 [0.73, 1.99], P = 0.476); myocardial infarction (I–III tertile, HR [95% CI] = 0.86 [0.55, 1.35], P = 0.509; clinically‐driven target lesion revascularization (I–III tertile, HR [95% CI] = 0.75 [0.53, 1.08], P = 0.123; definite or probable stent thrombosis (I–III tertile, HR [95% CI] = 0.98 [0.49, 1.99], P = 0.964. Conclusions: In the present study, the patients' body mass index was found to have no impact on long‐term clinical outcomes after coronary artery interventions. © 2015 Wiley Periodicals, Inc.